Narrativas do sol: (re)construção identitária do sertão em enunciados de mestres da cultura popular - Santos, Hugo Pedro Silva dos (2023)
The sertão/Northeast was invented through the consolidation of a hegemonic discursive matrix that implies to the territory a series of images and archives of social memory that refer to drought, extreme poverty, inclemency of space and, as an essential consequence, to the withdrawal and exodus. A large part of such socio-territorial, cultural and historical aspects were established through a hegemonic discursive matrix that brought together discursive processes in different spheres of human activity, according to the historiography of Albuquerque Jr. (2011; 2013). Among the spheres that contributed decisively to the invention of the Northeast/sertão, we can highlight the artistic-cultural sphere, especially with regard to what was called northeastern regionalism, a concept that defines the culture of the territory as traditional, archaic and mythical, corroborating for the consolidation of a supposedly essential identity for the space and its people. This time, the objective of this work is to understand how the identity of the sertão is discursively (re)constructed in statements by masters of popular/regionalist culture from the city of Piranhas/AL, state of Alagoas. That is, I intend to understand what world of meanings are present in oral statements by masters of regionalist popular culture from Piranha and what are the semantic and identity implications for the territory. For this purpose, I take as a corpus/materiality of studies, utterances by masters of regionalist popular culture from Piranhas/AL, generated in “controlled conversations” carried out with subjects recognized regionally as masters of regional culture of cultural manifestations such as the Samba from Tebei, Reisado, Grupo Armorial from Piranhas/AL and Xaxado from the city located in the high backlands of Alagoas. I am epistemologically affiliated with the theoretical-methodological assumptions of Applied Linguistics with an indisciplinary basis, an area of linguistic-discursive studies based on the concern to elaborate intelligibility about contemporary social life, the research is also anchored in the interpretivist epistemological paradigm, understood and modulated here, to the in the light of Bakhtinian studies, such as ethnolinguistics of living speech, which provides apparatus and theoretical-methodological subsidies for a discursive reading of the aforementioned materiality. Understanding the corpus of the research as complex, during the course of the investigation, knowledge from different areas of knowledge is mobilized, such as History, Geography, Linguistics, Cultural and Identity Studies, referring to the historiographical proposal of Albuquerque Jr. (2011, 2014, 2016, 2017, 2018 and 2020), as well as in the conception of Bakhtinian language in Bakhtin (2011, 2015, 2018) and Volóchinov (2018, 2019) as well as in the epistemological proposal of Moita Lopes (2006, 2009, 2020), Signorini (1998), Hall (2007; 2014), among others. The results reverberate the identity construction of the hinterland through the imbrication of two fundamental questions, culture and nature. The statements of the masters of popular culture build the sertão identity in dialogue with the hegemonic discursive matrix and with the regionalist political-literary proposal of the end of the century. XIX over the territory, so that the sun, for example, is chosen narratively as a striking symbol for the construction of such an aspect.